Investigation of Maximum Heat Transfer from an Aluminum Alloy Extended Surfaces - Raad Muzahem Fenjan (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2017)
The aim of this research is to obtain the maximum steady state heat transfer used aluminum alloy extended surfaces which obtain the optimal design for these fins. For three cases, (according to both dimension and direction of the extended surfaces): vertical fins extended from horizontal base, vertical fins extended from vertical base , and horizontal fins extended from vertical base, the natural convective, conductive and radiative heat transfer was studied experimentally and respectively the comparison between these cases were achieved. The parameters studied were distance between fins, fin length fin thickness and fin protrusion.